2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591297
|View full text |Cite
|
Sign up to set email alerts
|

Catheter simulator software tool to generate electrograms of any multi-polar diagnostic catheter from 3D atrial tissue

Abstract: Simulations are excellent tools for assessing new therapeutic strategies and are often conducted before implementing new therapy options in a clinical practice. For patients suffering from a heart arrhythmia, the main source of information comes from an intracardiac catheter. One of the common catheters is a Lasso multi-pole diagnostic catheter, which is a catheter that has 20 electrodes in a circular pattern. In this paper, we developed algorithm and simulation software that allows the users to place a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For each electrode, the electrogram was obtained as a weighted summation of the effects of every single cell considered as a dipole and a sampling frequency of 1 kHz ( Spach et al, 1979 ; Shillieto et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…For each electrode, the electrogram was obtained as a weighted summation of the effects of every single cell considered as a dipole and a sampling frequency of 1 kHz ( Spach et al, 1979 ; Shillieto et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the 2D simulations, the electrodes' coordinates were directly placed on the 2D tissue. For the simulations in the real 3D anatomy, we used our method [34] to project and register the plane of principal curvature of the catheter to the 3D surface. The unipolar electrode coordinates were used to acquire the transmembrane potentials from the corresponding location on the atrial tissue.…”
Section: Catheter and Electrogram Simulationsmentioning
confidence: 99%
“…It is also urgent to develop human circulation model simulators that do not need animal from the bioethical viewpoint. Recently, studies on virtual reality simulation have been reported [8][9][10], but it cannot reproduce the catheter insertion feeling or the sense of insertion length. Past studies on simulators have reported vascular models simulating the coronary artery, arteriovenous circulation in the arm, or a coronary circulation simulator for children [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%